(untitled) (Journal of Guidance and Counselling Studies, 2023)
Social Studies is one important subject in upper basic education level schools (JSS 1-3) that exposes students to innovations and creative tendencies. It is believed that the teaching and learning of Social Studies with blended learning will make retention easier and realizable. This research investigated Social Studies students’ performance and retention using blended learning in upper basic education level schools in Delta State. Four research questions and four hypotheses were used to guide the study. The research design for the study was a pre-test, post-test, control group, quasi experimental design with the population that comprised of all Social Studies students in public upper basic education level Schools in Ika North East Local Government Area of Delta State. A sample of 60 Social Studies students from three (3) non-equivalent intact classes were selected through purposive sampling technique. A validated researcher-made test titled Social Studies Performance Test (SSPT) consisting of 40 multiple choice items on the topic man and his environment in UBEL Schools 2 (JSS2) was used. Kuder-Richardson formula 21 was used to determine the reliability coefficient (r) and the reliability coefficient of the instrument was obtained as 0.69. The experimental group was taught using blended learning models as Social Studies station-rotation and Social Studies laboratory-rotation while the control group was taught using the conventional method. Social Studies Performance Test was administered to the two groups as pre-test and post-test. Retention test was administered to all the groups after three weeks of post-test. Mean and standard deviation were used for research questions and Analysis of Covariance was used to test the hypotheses at 0.05 alpha level. The findings of the study revealed that JSS2 Social Studies students taught using blended learning approach performed better than the conventional approach. The retention test showed that JSS2 Social Studies students’ retention ability was significantly higher in the experimental groups as against the control group. The study recommended that Social Studies teachers should be encouraged to use blended learning approach in learning process and Social Studies students should also be encouraged on the usefulness of this learning approach thereby helping to improve their academic performance in upper basic education level schools and beyond.